(untitled) (Bangladesh Journal of Scientific Research, 2016)
A pot experiment was conducted to investigate the effect of irrigation water collected from different industrial areas on Red amaranth (Amaranthus tricolor L.) and tomato (Solanum lycopersicum L.). Collected water samples were analyzed for various parameters, which include pH, DO, BOD, COD, P, NH3-N, K, S, Zn, Cu, Pb and Cd. The results were compared with the irrigation water quality standards by the Department of Environment (DoE) of Bangladesh and many of them were found several-folds higher than the permissible limit. The deterioration trends of the water samples are as follows: Tejgaon canal > Rampura canal > Sitalakhya river. Dry matter of vegetables grown on Tejgaon soil was significantly (p ? 0.05) higher than that of agricultural soil. Both red amaranth and tomato grown in Tejgaon soil accumulate highest concentration of heavy metals followed by Rampura and Sitalakhya soil. The concentrations of zinc (Zn), lead (Pb) and cadmium (Cd) in edible portions of both vegetables were found several times higher than the WHO prescribed permissible limits. The concentration of heavy metals in vegetables were found in the order Zn > Cu > Pb > Cd. Bangladesh J. Sci. Res. 28(2): 151-159, Dec-2015